Taxing Pollutuion: Agglomeration and Welfare Consequences - Marcus Berliant; Shin-Kun Peng; Ping Wang (European Regional Science Association (ERSA), 2012)
This paper demonstrates that a pollution tax with a fixed cost component may lead, by itself, to segregation between clean and dirty firms without heterogeneous preferences or increasing returns. We construct a simple model with two locations and two industries (clean and dirty) where pollution is a by-product of dirty good manufacturing. Under proper assumptions, a completely stratified configuration with all dirty firms clustering in one city emerges as the only equilibrium outcome when there is a fixed cost component of the pollution tax. Moreover, a stratified Pareto optimum can never be supported by a competitive spatial equilibrium with a linear pollution tax. To support such a stratified Pareto optimum, however, an effective but unconventional policy pre-scription is to redistribute the pollution tax revenue from the dirty to the clean city residents.
Keywords: D62; H23; R13; 330; Pollution Tax; Agglomeration of Polluting Producers; Endogenous Stratification